Microsoft .NET Framework 4.5 quickstart cookbook : get up to date with the exciting new features in .NET 4.5 framework with these simple but incredibly effective recipes /: get up to date with the exciting new features in .NET 4.5 framework with these simple but incredibly effective recipes. (2013) - Unknown
No abstract available